2021
DOI: 10.1088/1742-6596/1951/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Local structure and electronic structure of LiFePO4 as a cathode for lithium-ion batteries

Abstract: The local and electronic structure are significant to determine the performance of electrodes in lithium-ion batteries (LIB). Here we report the local structure of LiFePO4 as a cathode of LIB studied by Fe K-edge on X-ray absorption spectroscopy (XAS). The mixture of oxidation state of Fe ion (Fe2+/Fe3+) and the nearest neighbor of Fe atom were reported in this study. Furthermore, the preliminary study of electronic structure shown by the calculated density of states in antiferromagnetic spin configurations ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The normalized XANES spectrum for the Fe atom is shown that there are two peak energy areas, absorption edge area and pre-edge area (Astuti et al, 2021). Both of these areas show the XANES spectrum characteristics of absorber atom, which is Fe atom in this study.…”
Section: Resultssupporting
confidence: 50%
See 4 more Smart Citations
“…The normalized XANES spectrum for the Fe atom is shown that there are two peak energy areas, absorption edge area and pre-edge area (Astuti et al, 2021). Both of these areas show the XANES spectrum characteristics of absorber atom, which is Fe atom in this study.…”
Section: Resultssupporting
confidence: 50%
“…Both of these areas show the XANES spectrum characteristics of absorber atom, which is Fe atom in this study. In previous study, the spectrum and peak energy value (E0) of the Fe atom in the LiFeSixP1-xO4/C material for absorption edge area were 7124 -7125 eV (Maghfirohtuzzoimah et al, 2021;Astuti et al, 2021), while the spectrum of the Fe K-edge in Pre-edge area for standard sample and experimental sample is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations